Analisis psikologis dan gizi atlet untuk kejuaraan pekan olahraga Semarang 2023 - Yudha Kusuma, Donny Wira; Yuwono, Cahyo; Qoriah, Anirotul; Supriyono, Supriyono; Wiyanto, Agus (Universitas Nusantara PGRI Kediri, 2024)
Athlete psychology and nutrition play an important role in athlete success. These factors influence each other, so knowing athletes' psychology and nutrition levels is necessary. This study aimed to analyze the level of psychology and nutrition of athletes. The research method used in this study is a survey with an ex post facto research design. This research survey uses the distribution of questionnaires in accordance with the instruments used. The sample involved in this study were athletes who participated in the 2023 Provincial Sports Week championship (PORPROV), with the total sampling technique involving as many as 285 athletes. The analysis technique in this study uses descriptive quantitative to determine the mean and standard deviation and is categorized into 5 levels. From the results of the table analysis above, the psychological aspects of the 285 athletes involved in this study showed good results. The results of the table analysis above show that the nutritional adequacy of the 285 athletes involved in this study is sufficient. This study concludes that the psychological and nutrition of athletes need to be improved, given the importance of these factors as one of improving achievement.